INCREASING COMMUNITY KNOWLEDGE IN OVERCOMING FLOODS THROUGH COUNSELLING AS A FLOOD DISASTER MITIGATION EFFORT - Nur Hidayati; Karsim; Della Ika Aulia Safitri; Laeli Rahmawati; Resti Khoirotun Niswah (Journal of Community Research and Engagement, 2025)
Background: Flood disasters present a recurring challenge in Indonesia, particularly in low-lying regions like Sumberagung Village, Lamongan Regency, which is highly vulnerable to shallow river overflows. A critical barrier to community resilience is the lack of public understanding regarding disaster preparedness. Objective: This community service initiative aimed to enhance residents' knowledge through flood mitigation education and a targeted reforestation program. Methods: The intervention combined educational sessions on local flood risks and mitigation techniques with a collaborative tree-planting initiative. Diverse local stakeholders, including village officials and community members, actively participated in planting 65 trees at designated landslide-prone points. The efficacy of the educational component was evaluated using a quantitative pre-test and post-test design. Results: The evaluation demonstrated a significant increase in community knowledge, with average assessment scores rising from 51.87 in the pre-test to 76.87 in the post-test. Conclusion: The results indicate that structured educational activities are highly effective in raising public awareness and fostering a culture of disaster mitigation. To ensure long-term environmental conservation, future programs must establish community-led monitoring frameworks to sustain the newly planted trees.